Product’s material cost categories and measures - Kanerva, Viivi (My University, 2024)
Shipbuilding is a complex process where the selection of appropriate materials in the design phase ensure the ship's structural properties, performance and long lifetime. Shipbuilding aims to design and build a product meeting owner’s requirements while also securing sustainable product and long working life. The purpose of this thesis was to define and analyse measures to follow and compare the total material costs of a case company operating within a maritime industry. Accurate and easy to use cost follow-up measures are expected to improve the forecasting quality, identify the required action points and ease managing of the cost estimates. Within a competitive market and with low profit margins, the pricing of the product as well as managing the future company insights require accurate and reliable means to create the cost estimates. The literature review of the thesis started from describing the basic principles of ship design processes and material categorization and followed by presenting the key aspects of forecasting and cost estimation of shipbuilding materials. The thesis suggests material categories to support better material cost follow-up and comparison. The categories were defined based on the similar properties of the materials and typical categories presented by the literature. The selected and analysed material categories were stock materials, machinery systems, electrical systems, hotel systems and deck systems. As a result of the thesis, it was found that especially the materials with low individual price and high volume had a good linear dependency on the gross tonnage of the analyzed ship. The machinery system costs were well comparable to the installed power of the main engines. The categories containing more variation independent materials, especially the deck systems, were found to be more difficult to group and measure. The KPIs presented in this thesis are suitable for a high-level analysis and comparisons but a further investigation of the shown deviations would be recommended to reach results that are more accurate.
Keywords: material costs, material categorization, forecasting, ship